Respuestas

  • Usuario de Brainly
2013-06-06T04:37:09+02:00
3/4*2-4*(-1/2)-1,8=
3/2  + 2 - 18/10 =
15/10 + 20/10 - 18/10 =
17/10

6,2-3,4/(-2)+3/2 =
62/10 - 34/10 : (-2) + 3/2 =
62/10 + 17/10 + 3/2 =
62/10 + 17/10 + 15/10 =
94/10

(0,3+5/6)/0,1-5*81/16 =
(3/10 + 5/6)/ (1/10) -405/16 =
(18/60 + 50/60) / (1/10) - 405/16 =
  68/60 : 1/10 - 405/16 =
34/3 - 405/16 =
544/16 - 405/16 =
139/16

10/(1/6-1/3)+2(-1,4+0,2) =
10/(1/6 - 2/6) + 2(- 14/10 + 2/10) =
10/ (-1/6) + 2 ( - 12/10) =
- 60 - 12/5 =
- 312/5

(3/5+1/25-1/2)*5/6 =
(30/50 + 2/50 - 25/50) * 5/6=
 
7/50 * 5/6 =
35/300 =
7/60

espero que te sirva, salu2!!!!!